Digitized Child Monitoring System in Anganwadis - R., Vaishiya; M., Sree Sudharasan A; S., Sripoornimadevi T; M., Yuvasree; P., Malarvizhi (Recent Research Reviews Journal, 2025)
The Integrated Child Development Services (ICDS) program plays an important role in enhancing the health and nutrition of rural children in India through Anganwadi centers. However, these centers primarily rely on manual record-keeping, which is labor-intensive, error-prone, and inefficient. The absence of real-time data monitoring delays the detection of malnutrition and other health risks, making timely intervention challenging. Additionally, inadequate parental involvement and inefficient communication mechanisms delay effective follow-ups, while excessive administrative workloads divert Anganwadi workers' attention from childcare to cumbersome paperwork. The lack of a centralized digital database further complicates data retrieval and long-term health tracking, reducing the effectiveness of child welfare initiatives. A Digitized Child Monitoring System is proposed to address these challenges, integrating Radio Frequency Identification (RFID) based attendance tracking and automated Body Mass Index (BMI) measurement to ensure accurate and up-to-date health records. The system introduces a real-time alert mechanism that automatically sends Short Message Service (SMS) notifications to parents and relevant authorities when health issues are detected, enabling prompt action. A cloud-based database stores and analyzes child health records, facilitating data-driven decision-making and predictive analytics for early risk identification. The system also incorporates an intuitive dashboard for Anganwadi workers and healthcare officials, improving accessibility and usability. By streamlining digital record-keeping, facilitating real-time health monitoring, and automating communication, the system enhances transparency, minimizes manual labor, and improves overall child development outcomes. This approach ensures data accuracy, optimizes resource utilization, and strengthens the efficiency of the ICDS program in rural communities.
Keywords: Anganwadi; Child Health; RFID Attendance; Growth Monitoring; Automated Alerts; Early Intervention